2019
DOI: 10.1037/pas0000749
|View full text |Cite
|
Sign up to set email alerts
|

Is all nonhomeostatic eating the same? Examining the latent structure of nonhomeostatic eating processes in women and men.

Abstract: Nonhomeostatic eating is a complex (presumably) multidimensional construct associated with negative health outcomes. However, little research has examined the latent structure of nonhomeostatic eating processes, interrelationships among nonhomeostatic eating constructs, and differential associations between nonhomeostatic eating constructs and external correlates. This study adopted a construct validation approach to investigate these research questions in a large sample of undergraduate women and men (N ϭ 998… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 44 publications
2
8
0
Order By: Relevance
“…Further, these results suggest that emotion recognition of others -assessed via the RMET -also corresponds to emotion dysregulation and binge eating. Taken together, the present results reflect previous findings suggesting that men, more so than women, use binge eating as a maladaptive coping mechanism for emotional distress (Han and Pistole, 2014;Kukk and Akkermann, 2017;Racine et al, 2019).…”
Section: Main Effects Of Gendersupporting
confidence: 90%
See 1 more Smart Citation
“…Further, these results suggest that emotion recognition of others -assessed via the RMET -also corresponds to emotion dysregulation and binge eating. Taken together, the present results reflect previous findings suggesting that men, more so than women, use binge eating as a maladaptive coping mechanism for emotional distress (Han and Pistole, 2014;Kukk and Akkermann, 2017;Racine et al, 2019).…”
Section: Main Effects Of Gendersupporting
confidence: 90%
“…Female athletes were also partially defined by higher scores on the TAS-DDF, which, together with greater DERS and EDI-B, reflects previous work that found emotion dysregulation and alexithymia contribute to binge eating risk for female athletes (Wollenberg et al, 2015;Shriver et al, 2016). It may be that female athletes engage in binge eating as a means of emotion regulation, similar to men in the general population (Han and Pistole, 2014;Kukk and Akkermann, 2017;Racine et al, 2019). Female athletes also report higher perceived stress than male athletes and may binge eat as a coping mechanism (Williams, 2016).…”
Section: Interaction Of Athletics and Gendersupporting
confidence: 74%
“…Multiple lines of evidence suggest that individuals with FA have more depressive symptoms than controls [ 60 , 105 , 130 , 150 , 151 , 152 ]. A recent review of studies using YFAS identified depressive symptoms as a clinically relevant correlate [ 49 ].…”
Section: Other Psychiatric Diagnosesmentioning
confidence: 99%
“…The concept of FA posits that individuals experience addictive‐like symptoms related to the consumption of high‐calorie/palatable foods (Bonder, Davis, Kuk, & Loxton, ; Davis, ; Meule, von Rezori, & Blechert, ; such as preoccupation with obtaining a desired food, excessive consumption of unhealthy foods despite adverse health consequences, craving, impaired control, tolerance, withdrawal, and distress/dysfunction; Fletcher & Kenny, ; Gordon, Ariel‐Donges, Bauman, & Merlo, ), and with biological–hormonal maintaining factors (Novelle & Diéguez, ; Peters et al, 2018). It has been related to other addictive disorders due to the parallels in the neurochemistry (Gearhardt 2016; Jiménez‐Murcia et al, ; Tomasi et al, ), specifically in terms of participation of the dopaminergic reward system and the activation of positive reinforcement mechanisms (Carter & Davis, ; Racine, Hagan, & Schell, ; Volkow, Wang, Fowler, Tomasi, & Baler, ). This evidence suggests that FA could be evaluated by considering the behavioural and symptomatology patterns observed in other addictions, as captured in the Yale Food Addiction Scale (YFAS; Gearhardt, Corbin, & Brownell, ).…”
Section: Introductionmentioning
confidence: 99%